The Xenes Generations: A Taxonomy of Epitaxial Single‐Element 2D Materials. Issue 2 (7th October 2019) - Grazianetti, Carlo; Martella, Christian; Molle, Alessandro
Abstract : Isolation of graphene is today a milestone in condensed matter physics that paves the way to a new entire class of 2D synthetic materials referred to as Xenes with no analogous bulk layered allotropes. The booming rush to discover first novel and unprecedented materials flows into two generations of Xenes: the first one strictly relates to carbon being made of elements of the IV/14 column/group of the periodic table, and the second one includes elements of the adjacent columns. From borophene to tellurene, with rare exceptions, the physics and chemistry of the elements are rewritten and herein reviewed in terms of their fundamental and peculiar properties. Particular attention is paid to the epitaxial methodologies and configurational details, aiming at determining key points for nanotechnology applications of the Xenes afforded by scalability, quality, and stability aspects. Finally, the ongoing efforts to devise and realize applications based on the Xenes are summarized. Abstract : The novel class of monoelemental two‐dimensional materials termed Xenes is reviewed and classified into two generations. The attention is turned on the epitaxial methodologies for their synthesis and on several key points, such as scalability, quality, and stability, which enable the Xenes exploitation in a wealth of technological applications including the integration into ultrascaled functional devices.